Sound-driven dissipative self-assembly of aromatic biomolecules into functional nanoparticles. Issue 3 (23rd December 2019) - Bhangu, Sukhvir Kaur; Bocchinfuso, Gianfranco; Ashokkumar, Muthupandian; Cavalieri, Francesca
Abstract : The out-of-equilibrium self-assembly of simple aromatic amino acid molecules is driven by high frequency ultrasound, where acoustic energy acts as a fuel to form uniform supramolecular nanostructures with multifarious optical and biological properties. Abstract : Dissipative self-assembly processes were recently exploited to assemble synthetic materials into supramolecular structures. In most cases, chemical fuel or light driven self-assembly of synthetic molecules was reported. Herein, experimental and computational approaches were used to unveil the role of acoustic cavitation in the formation of supramolecular nanoaggregates by dissipative self-assembly. Acoustic cavitation bubbles were employed as an energy source and a transient interface to fuel and refuel the dissipative self-assembly of simple aromatic biomolecules into uniform nanoparticles. Molecular dynamics simulations were applied to predict the formation of metastable aggregates and the dynamic exchange of the interacting molecules in the nanoaggregates. The intracellular trafficking and dissipative dissolution of the nanoparticles were tracked by microscopy imaging.